The triad «education-science-innovation»: indicators and challenges for Belarus - Druk, V.Yu.; Verich, A.I. (Экономика и банки, 2025)
Objective – to analyze the trends in the development of higher education in the context of its interaction with scientific-innovation activity, as well as in the identification of regularities and stable relations of the triad “education-science-innovation” in the context of their impact on the economic security of the country. Materials and methods. The study was carried out on the basis of statistical data characterizing the spheres of «education» and «science and innovation». General (analysis, observation, measurement, comparison) and special (statistical-economic, data visualization) methods of scientific research were applied. Results. The article analyzes the dynamics of specific indicators characterizing the innovation potential of education and science for the period 2016-2023, studies the performance of innovation activity of the national economy. It is concluded that the identified negative trends (decrease in the share of the higher education sector in R&D, low share of education expenditures in the total amount of budget expenditures, decrease in the share of persons who graduated from postgraduate education with the defense of a thesis for the degree of candidate or doctor of sciences, steady decrease in the number of students in the total population, decrease in the inventive and patent activity of national applicants) can significantly limit the potential of the education system in the field of innovation and scientific development of the national economy. It is stated that the establishment of patterns that determine the successful interaction between education, science and innovation will allow to create a model that promotes a more effective exchange of knowledge and resources. Conclusion. The research is aimed at creating an effective strategy of interaction between education, science and innovation, which will have a positive impact on innovation activity and, ultimately, will contribute to sustainable economic growth and increase the competitiveness of the country. Thus, the results of the study will allow not only to identify sustainable interrelationships in the triad “education-science-innovation”, but also to develop practical recommendations that will help to create a harmonious ecosystem for innovative development.